Students' engagement and performance of the science subject: a study based on tellippalai divisional school - Raveeswaran, M.; Maithily, R. (University of Jaffna, 2022)
Purpose: Currently, the science achievement of students in schooling is influenced by several factors which has proven by researchers. Hence, the present study is aimed to analyze how the student engagement related and impacted on science achievement in Tellippalai Divisional school of Valikamam Zone, Sri Lanka. Methodology: For this study, survey strategy was used and 212 school students were selected randomly among the 729 total population. The data was collected through standard questionnaire which consist three parts. Part one consisted data related with background factors of participants. Part two included the questions of measuring student engagement and part three consisted science achievement of the respondents. Data were analyzed by using SPSS 20.0 version. The techniques adapted for the present study were correlation and regression analysis. Findings: The statistical analysis revealed that there is significant and positive relationship between students' engagement and students' achievement of science. Also it has proven that there is a significant impact of students' engagement on science achievement which ensure that the developed two hypotheses were accepted in this study. Therefore, all components of engagement such as behavioral, cognitive and emotional engagement were correlated with science achievement in Tellippalai Divisional school of Valikamam Zone, Sri Lanka. Research limitation: In the present study, the researchers only consider the science achievement of Valikaman Zonal' students. There are ninety six Educational Zones in Sri Lanka. In order to provide valuable inputs to the policy makers, this study should be extended to all the Zones in Sri Lanka. The future researchers can consider moderating and mediating variables like students' characteristics and family support to confirm the relationship between engagement and achievement. Implications: Valikamam Zone is the strongly war affected area in Jaffna District. Further the economic position of parents is also very poor because they lost most of their agriculture lands because of local war existed for more than fifty years. Hence the students' education position is also poor. That has been proofed by Valikamam Zone is at 92 rank among nighty six zone in Sri Lanka in 2019 G.C.E ordinary Level result. Burden responsibility is laying on educators and policy makers to improve the level of achievement by increasing the level of engagement. One way to improve student engagement is to create an environment in which students are challenged to meet high expectations but that also makes them feel comfortable asking questions. This is crucial, because students who feel challenged by their work are less likely to say they are bored, or to disengage. Hence it is better to adopt student centered teaching and learning method. Moreover, it is the primary responsibility of teachers, parents, educators and policy makers to include ways of improving engagement in curriculum and by which it is possible to increase the level of students' achievement.
Keywords: Behavioral engagement; Cognitive engagement; Emotional engagement; Engagement; Science achievement